Tinjauan Yuridis Penerapan Sanksi Pidana bagi Pengguna Jasa Prostitusi Anak Berdasarkan Teori Keadilan - Dayana, Puspita Sandra; Cornelis, Vieta Imelda; Soekorini, Noenik; Astutik, Sri (LPPM Institut Pendidikan Nusantara Global, 2025)
The development of information technology has facilitated the rise of online child prostitution cases in Indonesia; however, the application of criminal sanctions against perpetrators has yet to fully reflect the principle of justice. This study aims to analyze the application of criminal sanctions for users of child prostitution services based on the theory of justice, through a case study of Decision Number 1172/Pid.Sus/2024/PN Sby. The research employs a normative legal approach with normative juridical techniques. The research population includes all legal materials related to criminal sanctions for child prostitution, with the sample consisting of court decisions, statutory regulations, and legal literature selected through purposive sampling. The research instruments include a document analysis guide, with data analyzed using normative descriptive-analytical qualitative techniques. The findings show that the judge imposed a prison sentence of 4 years and a fine of IDR 120,000,000 under the Human Trafficking Law, rather than the Child Protection Law as demanded by the prosecutor. The judge's considerations emphasized mitigating factors more than the protection of the child victim. The study concludes that the application of criminal sanctions has not been optimal in providing a deterrent effect and delivering justice to victims, thus highlighting the need for policy reform with stricter sanctions and sentencing guidelines that prioritize the best interests of the child.